2012
DOI: 10.1108/17410391211245829
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of informal coordination in networked supply chains

Abstract: Abstract:Purpose -Provide insight into the determinants or constructs that enable informally networked supply chains to operate in order to achieve improved operational performance. Design/methodology/approach -The research is based on a wide literature review, focused on the identification of dimensions of informal networking in supply chains along network connectivity, supply chain relationship alignment, informally networked supply chain, and operational performance. These determinants or constructs of info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 80 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…Collaboration can be vertical or horizonal [40], in this paper we focus on SC collaboration in general. SC risks are challenges linked to potential disturbances influencing SC partners that may directly influence an organization's capability to operate, produce goods, or offer services [41]. As SMEs have fewer financial resources to cope with emerging risks and prevail over them upfront, the implementation of a proper RM within the SC lacks [19,22].…”
Section: Risk Management In Supply Chains In Smesmentioning
confidence: 99%
“…Collaboration can be vertical or horizonal [40], in this paper we focus on SC collaboration in general. SC risks are challenges linked to potential disturbances influencing SC partners that may directly influence an organization's capability to operate, produce goods, or offer services [41]. As SMEs have fewer financial resources to cope with emerging risks and prevail over them upfront, the implementation of a proper RM within the SC lacks [19,22].…”
Section: Risk Management In Supply Chains In Smesmentioning
confidence: 99%
“…Better coordination and resource sharing in the supply chain are derived from integrating the supply chain in an organization that allows a whole information flow. Some scholars confirmed that coordination and sharing of resources positively affect the supply chain operational performance and efficiency (Huo et al, 2015;Jiang et al, 2007;Ogulin et al, 2012;Soroor et al, 2009). It is crucial, though, for the managers to focus on improving the coordination of the supply chain by comparing and evaluating the organizational issues to trigger responsiveness and culture (Singh et al, 2019).…”
Section: Theme Iii: Processesmentioning
confidence: 99%
“…This includes the development and maintenance of capabilities to ensure the effective delivery of medical products and services. 34 proposed strategic alliances between the organization and suppliers, manufacturers, and distributors to produce and market ACTs. These scholars demonstrated the relevance of the development of coordination frameworks to enhance the strategic management of ACTs, and argued that the interaction of the micro-market and macro environments is vital for the supply and distribution of ACTs.…”
Section: Hypotheses Developmentmentioning
confidence: 99%